Pengaruh umur dan pengalaman inseminator terhadap keberhasilan inseminasi buatan pada sapi perah di wilayah kerja Koperasi Peternak Sapi Bandung Utara (KPSBU) Lembang - Rifki Jihadi Asyraf; Ajat Sudrajat; Setyo Utomo; Raden Febrianto Christi (Fakultas Pertanian Universitas Majalengka, 2023)
This study aimed to evaluate the success rate of artificial insemination (AI) in dairy cows at KPSBU Lembang District based on experience and different ages of inseminators. The research was carried out on December 26, 2022 - January 31, 2023, in Lembang District. The research was conducted using a survey method and the variables measured were the success of artificial insemination including service per conception (S/C), Conception Rate (CR), Non-Return Rate (NRR), and Calving Interval (CI). Data analysis used in this study is a simple correlation analysis and quantitative descriptive. The results showed that the average age of the inseminator was 39 years old, the average inseminator work experience was 19 years. Meanwhile, the average of S/C value was 1.84 time, the CR value was 64.50%, the NRR value was 93%, and CI value with an average of 13 months. The correlation analysis showed that (X) experience and age have no significant effect (p>0,05) on the success of AI based on (Y) S/C and CR. It can be concluded that the success rate of artificial insemination of dairy cows based on S/C and CR in Lembang District was good, but the experience and age of inseminators had not affected the success of artificial insemination in Lembang District